Fundamentos da fotoeletrólise da água com dióxido de titânio - Ribeiro, Rafael Iacovanduano de Almeida (Universidade Federal de São Carlos, 2026)
Low-carbon hydrogen production presents itself as a promising advance in the quest for clean and sustainable energy sources, driving the global energy transition. More than just an alternative, this energy vector has the potential to significantly reshape the current energy landscape. In this context, titanium dioxide (TiO2) emerges as a prominent photoactive material for hydrogen production, due to its ability to catalyze the occurrrence of water electrolysis reaction under light irradiation, establishing it as one of the most promising and investigated materials in the field. This work aims to revisit and analyze the advantages and challenges inherent to the use of TiO2 in this context, as well as to explore the various factors that influence its efficiency and potential.
Fundamentals of water photoelectrolysis with titanium dioxide
Keywords: Dióxido de titânio; Hidrogênio de baixo carbono; Transição energética; Fotoeletrólise; Titanium dioxide; Low carbon hydrogen; Energy transition; Photoeletrolysis; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; 7. Energia limpa e acessível; 13. Ação contra a Mudança Global do Clima